1982
DOI: 10.1037/0022-006x.50.4.488
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between conceptual tempo and depression in children.

Abstract: The Matching Familiar Figures Test performances of 53 children in Grades 5 and 6 identified as being depressed on the basis of self-report questionnaires were compared to performances of 53 nondepressed children. The depressed group had longer latencies, made more errors, and was less efficient, even when intellectual differences were taken into account. Implications of these findings for the concept of childhood depression are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1

Year Published

1985
1985
1996
1996

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 10 publications
1
7
1
Order By: Relevance
“…Whether severe depression is the precursor of reduced cognitive functioning or whether impaired cognitive functioning produces depression cannot be determined from the present data. These findings of an inverse relation of depression to cognitive functioning are in agreement with certain prior studies (Kaslow, Tanenbaum, Abramson, Peterson, & Seligman, 1983;Schwartz, Friedman, Lindsay, & Narrol, 1982; but are not in accord with others (Kashani et al, 1983;Weinberg & Rehmet, 1983).…”
Section: Discussionsupporting
confidence: 80%
“…Whether severe depression is the precursor of reduced cognitive functioning or whether impaired cognitive functioning produces depression cannot be determined from the present data. These findings of an inverse relation of depression to cognitive functioning are in agreement with certain prior studies (Kaslow, Tanenbaum, Abramson, Peterson, & Seligman, 1983;Schwartz, Friedman, Lindsay, & Narrol, 1982; but are not in accord with others (Kashani et al, 1983;Weinberg & Rehmet, 1983).…”
Section: Discussionsupporting
confidence: 80%
“…Support for this theoretical contention has been reported for youngsters with self-reported depressive symptoms (Haley, Fine, Marriage, Moretti, & Freeman, 1985; Leitenberg, Yost, & CarrolWilson, 1986). This stands in contrast to some early research with depressed youngsters where the investigators reported that children who reported elevated levels of depressive symptoms experienced a deficit in information processing (Schwartz, Friedman, Lindsay, & Narrol, 1982). Results of a series of three investigations (Kendall, Stark, & Adam, 1990) were consistent with cognitive theory and indicated that depressed youngsters suffered from a distortion in self-evaluative information processing and did not suffer from a deficit in active information processing.…”
Section: Empirical Evaluation Cognitive Theory Of Depressioncontrasting
confidence: 50%
“…The 13-item short form of the Children’s Depression Inventory (CDI; Kovacs & Beck, 1977) was used to provide a self-report of the child’s depression level. The 15-item short form of the Piers-Harris Children’s Self-Concept Scale ( PHCSC ; Piers, 1984; Schwartz, Friedman, Lindsay, & Narrol, 1982) was used to provide a self-report of each child’s self-esteem.…”
Section: Methodsmentioning
confidence: 99%